2011
DOI: 10.1016/j.jds.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different air-abrasion particles on metal-ceramic bond strength

Abstract: Background/purpose: Chipping and delaminating of veneering ceramics are critical problems in the fabrication of metal-ceramic restorations. The purpose of this study was to evaluate the effect of different air-abrasion particles on the shear bond strength of a ceramic to nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr) alloys. Materials and methods: Forty square specimens (10 mm  10 mm  1.5 mm) were cast for each Ni-Cr and Co-Cr alloys. Specimens were divided into four groups for the air-abrasion procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…This bond depends directly on the formation of an oxide layer on the surface of the metal before firing the ceramic [4][5][6] . The control of this layer can be facilitated by APA using Al 2 O 3 , which also increases the area and the degree of wettability of the metal framework for the application of the ceramic 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This bond depends directly on the formation of an oxide layer on the surface of the metal before firing the ceramic [4][5][6] . The control of this layer can be facilitated by APA using Al 2 O 3 , which also increases the area and the degree of wettability of the metal framework for the application of the ceramic 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports have claimed, however, that this process may compromise the marginal integrity of the metal, and that damage is directly proportional to the size of the Al 2 O 3 particle [23][24][25] . In a study comparing metal-ceramic adhesion in Co-Cr and Ni-Cr alloys, there was a better bond strength in specimens that used Al 2 O 3 particles 110 μm in size 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Külünk et al 21) used 50 and 110 µ alumina particles to determine the effect of alumina particle size on metal-ceramic bond strength and concluded that higher bond strength values were obtained with 110 µ alumina particles. On the other hand, the difference of chemical composition and stiffness between Co-Cr and Ni-Cr alloys may also affect the surface roughness of tested metal surfaces after a standard sandblasting procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although not completely defined, they claimed that the adhesion between ceramic and metal depends on suitable oxidation of the metal and interdiffusion of ions between metal and ceramic. Additionally, Külünk et al 21) reported that the bond strength between ceramic and casting alloy is determined by the strength of chemical bonds, mechanical interlocking, the type and concentration of defects at the interface, wetting properties, and the degree of compressive stress in the ceramic layer due to differences in the coefficients of thermal expansion between the metal and ceramic.…”
Section: Introductionmentioning
confidence: 99%